EFL students’ perceptions of using the “Learn English with TV Series” YouTube channel as supplementary learning material - Hasanah, Siti Noor Syifa; Rizal, Daviq (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2024)
Digital platforms have increasingly become essential tools for enhancing English as a Foreign Language (EFL) learning, particularly in contexts where exposure to authentic language use is limited. YouTube, as one of the most widely used platforms, provides accessible, engaging, and authentic learning resources for EFL learners. Among the available channels, “Learn English with TV Series” has gained popularity due to its use of authentic scenes from popular TV shows to teach vocabulary, pronunciation, grammar, and communication strategies. This study aims to examine EFL students’ perceptions of using this YouTube channel as supplementary learning material. Employing a quantitative descriptive design, data were collected through an online survey administered to 100 EFL students from various regions in Indonesia. The findings indicate overwhelmingly positive perceptions: students frequently engage with the channel, find the content interesting and easy to understand, and perceive it as beneficial for developing listening, speaking, vocabulary, and grammar skills. The channel also enhances students’ motivation to practice English and is widely recommended among peers. These results demonstrate the channel’s potential as an effective supplementary resource to support formal English instruction. The study highlights the importance of integrating digital learning tools into EFL pedagogy and offers insights for educators and content creators in designing engaging and pedagogically sound online learning materials.